2009
DOI: 10.1021/jm900411s
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Inhibitor of Nipah Virus Envelope Protein-Mediated Membrane Fusion

Abstract: Nipah virus (NiV), a highly pathogenic paramyxovirus, causes respiratory disease in pigs and severe febrile encephalitis in humans with high mortality rates. On the basis of the structural similarity of viral fusion (F) proteins within the family Paramyxoviridae, we designed and tested 18 quinolone derivatives in a NiV and measles virus (MV) envelope protein-based fusion assay beside evaluation of cytotoxicity. We found five compounds successfully inhibiting NiV envelope protein-induced cell fusion. The most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…Molecular modelling indicated that one compound fitted well into a cavity present in the NiV F protein. This compound inhibited NiV-induced cell fusion but not MV-induced cell fusion, thus underlining specific differences between morbillivirus and henipavirus F proteins (Niedermeier et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Molecular modelling indicated that one compound fitted well into a cavity present in the NiV F protein. This compound inhibited NiV-induced cell fusion but not MV-induced cell fusion, thus underlining specific differences between morbillivirus and henipavirus F proteins (Niedermeier et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…They interfere with the conformational changes of the F protein at the beginning of the fusion process (Plemper et al, 2004(Plemper et al, , 2005Sun et al, 2006). Given the structural similarity of paramyxovirus F proteins, we tested some of these smallmolecule inhibitors and several derivatives in a NiV F proteinbased fusion assay (Niedermeier et al, 2009). Molecular modelling indicated that one compound fitted well into a cavity present in the NiV F protein.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of a high throughput screening assay has recently allowed the identification of a broad-spectre, small antiviral molecule, capable of inhibiting cleavage of the glycoprotein of several highly pathogenic viruses in vitro, including NiV, HeV and Ebola virus [91]. In addition, other quinolone derivate specifically designed to fit into a cavity of the NiV F protein involved in the fusion process showed an important capacity of inhibiting syncytia formation [92]. Development of new strategies to screen viral entry inhibitors under BSL2 conditions, transposable to BSL3 and 4 associated pathogens [93] has recently opened novel perspectives for the more rapid identification of new antiviral components and identification of new compounds will certainly follow.…”
Section: Small Moleculesmentioning
confidence: 99%
“…These types of heterocyclic compounds exhibit antitumor (8,9) anti-inflammatory (10,11), antibacterial (12), antiviral (13), and antimicrobial (14) activities. Since this investigation deals with a new approach to synthesize these medicinally important heterocyclic compounds, it is essential to review the procedures reported in literature.…”
Section: Introductionmentioning
confidence: 99%